Fine Grinding Of Silica Via Stirred Milling - Mohd Za’i, Mohamad Zulhakimi Haiqal (Universiti Sains Malaysia, 2022)
The ultrafine grinding occurs in different types of high energy mills, which the most common are vibratory, air-jet and stirred media mills. Stirred media milling is an effective means of grinding into very fine particle sizes is facing high demand from industry but yet has to determine the best practice to enhance the quality of product from fine grinding in term of size and shape distribution. As a result, the best practice as far as the characteristics of the stirred mill to be utilized, as well as the optimum dosage of grinding additives to be used during the grinding operation, will be investigated in this study. The main aim is to investigate the effect of various kind of grinding additives, i.e., methanol, triethanolamine, and sodium oleate, used during grinding operation towards the particle size and shape analysis of mineral, determine the optimum dosage of grinding additives and machinery operational parameters to produce good quality of product for industrial purpose. In this experiment, grinding additives such as methanol, triethanolamine (TEA), and sodium oleate will be used in dosages ranging from 0.25 percent to 2.00 percent, at 100 rpm to 400 rpm in range. Characterization tests such as the Particle Size Analyzer (PSA), X-Ray Diffraction (XRD), and Tabletop Scanning Electron Microscope (SEM) will be evaluated after the product has been discharged from the ceramic jar. The particle size distribution curves display by grinding with addition of TEA and sodium oleate shown highest size reduction to occur, with agitator speed adjusted to the highest level in this experiment (400 rpm). The success of this work will help in producing product of silica with good particle distribution and properties as expected to be shown by particle shape and particle size analysis.